2015
DOI: 10.1167/tvst.4.5.10
|View full text |Cite
|
Sign up to set email alerts
|

Reengineering Human Bruch's Membrane Increases Rod Outer Segment Phagocytosis by Human Retinal Pigment Epithelium

Abstract: Purpose: We have shown previously that Bruch's membrane (BM) aging decreases retinal pigment epithelium (RPE) phagocytosis. Herein, we determine the effects of BM reengineering on RPE phagocytosis.Methods: BM explants were dissected from young and old donor eyes. Some old BM explants were reengineered by cleaning with Triton X-100 and/or coating with extracellular matrix (ECM) ligands. ARPE-19 cell-derived ECM (ARPE-ECM) modified (''aged'') by sodium nitrite was subjected to similar treatments. ARPE-19 cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 52 publications
2
21
0
Order By: Relevance
“…We devised a model for age‐related changes to Bruch's membrane that is based on nonenzymatic nitration of extracellular matrix (ECM) that allows one to study RPE dysfunction in a compromised subretinal environment. The tissue culture method was validated ex vivo using aged or diseased Bruch's membrane …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We devised a model for age‐related changes to Bruch's membrane that is based on nonenzymatic nitration of extracellular matrix (ECM) that allows one to study RPE dysfunction in a compromised subretinal environment. The tissue culture method was validated ex vivo using aged or diseased Bruch's membrane …”
Section: Introductionmentioning
confidence: 99%
“…The tissue culture method was validated ex vivo using aged or diseased Bruch's membrane. 19,[32][33][34][35] A new generation of culture models uses human-induced pluripotent stem cells (iPSCs) that are generated from adult somatic cells harvested from patients with AMD and other macular dystrophies. 29,36,37 These studies have shown that complement and inflammatory markers are upregulated in iPSC-derived RPE cells from patients with macular degenerations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, aging of human BM, or damage induced by surgical manipulation of choroidal neovascularization, can reduce the ability of transplanted RPE cells to attach to human BM, survive after transplantation, and proliferate to repopulate this structure [42,45,48,49]. Aging of human BM also reduces the ability of human RPE cells seeded on this surface to ingest rod outer segments [50]. Thus, it is clear that in the advanced stages of AMD, namely GA, age-related changes to BM can adversely affect the successful transplantation of cells.…”
Section: Amd and Bruch’s Membrane Pathologymentioning
confidence: 99%
“…Thus, it is clear that in the advanced stages of AMD, namely GA, age-related changes to BM can adversely affect the successful transplantation of cells. Interestingly, we have previously shown that non-enzymatic nitration of the basement membrane is a relevant model system to study BM pathology and can affect RPE dysfunction, such as altered VEGF secretion, phagocytic ability, and expression of complement regulatory proteins in a manner that mimics the effects of BM aging in AMD [50,51,52,53]. We have further shown that cleaning and coating the surface of BM or nitrite-modified extracellular matrix (ECM) with such proteins as laminin, fibronectin, and vitronectin can reverse the effects of damage associated with an aged and/or diseased BM [52,54].…”
Section: Amd and Bruch’s Membrane Pathologymentioning
confidence: 99%